Persistance Rational Choice Pada Pemimpin Dalam Organisasi; Slr Dan Bibliometric - Ahmad Gunawan; Imam Sucipto (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The rational choice model is one of the most dominant paradigms in leadership studies. This paradigm is based on the assumption that leaders are rational and strive to maximize their goals. However, empirical studies show that leaders often do not behave rationally. This study aims to examine the persistence of rational models of choice in leadership studies. This study used systematic literature review (SLR) and bibliometric methods. Data were obtained from 100 scientific articles published in leading leadership journals. Data analysis was carried out using content analysis and bibliometric methods. This research is expected to have some implications for leadership studies. First, leadership researchers need to be more critical in using rational models of choice. Second, leadership researchers need to develop new models that can explain leaders' irrational behavior and are influenced by non-rational factors. Keywords: Persistance Rational choice, leadership, organization, SLR, bibliometric.